2003
DOI: 10.1101/gr.681703
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of a Functional Drosophila Centromere

Abstract: Centromeres are the site for kinetochore formation and spindle attachment and are embedded in heterochromatin in most eukaryotes. The repeat-rich nature of heterochromatin has hindered obtaining a detailed understanding of the composition and organization of heterochromatic and centromeric DNA sequences. Here, we report the results of extensive sequence analysis of a fully functional centromere present in the Drosophila Dp1187 minichromosome. Approximately 8.4% (31 kb) of the highly repeated satellite DNA (AAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
137
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 85 publications
16
137
0
1
Order By: Relevance
“…There are very limited data sets on the literature concerning the analysis of satDNA junctions under this context, but they generally support the expectations of the model (McAllister and Werren, 1999;Schueler et al, 2001;Mravinac and Plohl, 2007). The homogeneity of a junction between the AATAT and TTCTC satellites in the D. melanogaster Dp1187 minichromosome is an exception (Sun et al, 2003). Probably other molecular mechanisms, such as replication slippage, might be important in the homogenization and amplification of simple satDNA repeats.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…There are very limited data sets on the literature concerning the analysis of satDNA junctions under this context, but they generally support the expectations of the model (McAllister and Werren, 1999;Schueler et al, 2001;Mravinac and Plohl, 2007). The homogeneity of a junction between the AATAT and TTCTC satellites in the D. melanogaster Dp1187 minichromosome is an exception (Sun et al, 2003). Probably other molecular mechanisms, such as replication slippage, might be important in the homogenization and amplification of simple satDNA repeats.…”
Section: Discussionmentioning
confidence: 71%
“…For example, in D. melanogaster, a different set of satDNA families are often located near one another on the same chromosome (Lohe et al, 1993) and sequence analysis of a 31 kb DNA centromeric region from the X-derived Dp1187 minichromosome revealed that the highly repeated satellites AATAT and TTCTC are organized in uniform arrays directly juxtaposed, with neither interspersion nor intervening DNA (Sun et al, 2003). In humans, the centromeric region of each chromosome contains at least one a-satellite DNA together with a unique combination of other satDNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Centromeres are regions with lower recombination frequency (Beadle, 1932;Clarke and Carbon, 1980) and often exhibit interspersion of satellite sequences and TEs, as in cereals (Zhong et al, 2002), Arabidopsis (Copenhaver et al, 1999), insects (Sun et al, 2003) and fungi (Cambareri et al, 1998). There are indications of the evolutionary link between the centromere structure and TE's activity: centromeric satellite repeats may arise from DNA transposons (Kapitonov and Jurka, 1999).…”
Section: Processes Acting In Regions Of Reduced Recombinationmentioning
confidence: 99%
“…In contrast, the centromeres in eukaryotes that have been investigated are regions that vary in size from several hundred kilobases to a few megabases, such as fission yeast (S. pombe;Baum et al 1994), fruitfly (Drosophila melanogaster; Sun et al 1997Sun et al , 2003, and A. Kumekawa et al 2000Kumekawa et al , 2001Hosouchi et al 2002).…”
Section: Discussionmentioning
confidence: 99%